Conversational Implicature Found in Inside Out 2 Movie - Putu Radia Kalyana Pramadicha; I Nyoman Tri Ediwan; Gek Wulan Novi Utami (Pusat riset dan Inovasi Nasional, 2025)
This study investigates conversational implicature in the 2024 animated film Inside Out 2 by analyzing characters’ utterances through the lens of Grice’s theory of implicature and cooperative principles. Conversational implicature refers to the implied meanings not directly expressed but inferred through contextual understanding. Employing a qualitative descriptive method, this study examines both particularized and generalized implicatures, drawing data from selected dialogues in the film and its official transcript. The emotional complexity of the movie—highlighted by the presence of characters such as Anxiety, Envy, and Embarrassment—provides rich ground for analyzing indirect communication. Findings show that from 28 data items, 25 are particularized implicatures and 3 are generalized. This distribution emphasizes a strong reliance on context-sensitive communication, where meaning emerges from emotional, psychological, and situational cues. Particularized implicatures often occur in emotionally charged interactions, reflecting the characters’ internal struggles and development, particularly Riley’s journey through adolescence. Generalized implicatures, though less frequent, serve to convey socially shared assumptions, enhancing audience understanding in broader, often humorous contexts. The analysis also highlights how the characters’ utterances align with Grice’s maxims. The maxim of relevance is maintained through contextually appropriate responses; the maxim of quantity appears when speakers provide adequate information; the maxim of quality surfaces through honest and sincere exchanges; and the maxim of manner is evident in clear, concise communication. Together, these implicatures and maxims enrich the film’s emotional depth and narrative subtlety.